A randomised clinical trial to determine the abrasive effect of the tongue on human enamel loss with and without a prior erosive challenge. (March 2017) - Seong, J.; Claydon, N.; Macdonald, E.; Garner, S.; Newcombe, R.G.; West, N.
Abstract: Objectives: To investigate the abrasive effect of the tongue on human enamel loss with and without a prior dietary acid challenge in an in situ model. Methods: A single centre, single blind, randomly allocated, split mouth, four treatment regimen, in situ study in healthy adult volunteers was undertaken. Twenty four subjects wore two lower intra-oral appliances each fitted with 4 human enamel samples 6 h/day for 15 days. The samples were treated with either 50 ml orange juice or water for 5 min ex vivo 4 x/day; prior to being licked or not licked with the subject's tongue for 60 s. There were 2 samples per group per subject. Surface loss was measured by contact profilometry. Results: 23 subjects completed the study with no adverse events. The mean loss of enamel at 15 days was: 0.08 μm for water without licking, 0.10 μm with water and licking; 1.55 μm with orange juice alone, 3.65 μm with orange juice and licking. In the absence of erosive challenge, licking had no detectable effect on enamel loss p = 0.28. Without licking, orange juice had a highly significant effect on loss compared to water, p < 0.001. Erosive challenge followed by licking more than doubled the loss of enamel p < 0.001. Conclusions: When enamel was exposed to orange juice prior to licking, tissue loss as a result of tongue abrasion of the eroded surface was increased, and double that of the erosive challenge alone. Licking enamel with the tongue had no perceptible effect on enamel loss in the absence of the erosive challenge. Clinical significance: Enamel wear resulting from tongue abrasion on tooth surfaces softened by acid challenge, can be an unavoidable consequence of oral function. This may account for the pattern of erosive toothwear on palatal and occlusal tooth surfaces, reinforcing the importance of restricting the frequency of dietary acid challenge in susceptible individuals.